Influence of maternal characteristics and gestational age on hemodynamic indices: NICOM device‐specific reference ranges. (6th October 2019) - Perry, H.; Stirrup, O.; Gutierrez, J.; Vinayagam, D.; Thilaganathan, B.; Khalil, A.
ABSTRACT: Objectives: To construct reference ranges for stroke volume, cardiac output and systemic vascular resistance (SVR) in normal pregnancy for the NICOM® device, and to explore associations between maternal characteristics and these hemodynamic variables. Methods: This was a prospective cohort study of healthy singleton pregnancies between 10 and 40 weeks' gestation attending a tertiary referral hospital between September 2012 and May 2018. Measurements of stroke volume, cardiac output and SVR were obtained throughout pregnancy using NICOM, a non‐invasive device based on bioreactance technology. NICOM device‐specific reference ranges were created with respect to gestational age and maternal characteristics. Once the distribution of the data had been determined with respect to the gestational age, patient characteristics were added to the model to test whether they provided a significant improvement in prediction of the median value. The effect was assessed of maternal weight, height, smoking status, conception using assisted reproductive technology, nulliparity and ethnicity. Results: We included 411 women in this study. The relationships between cardiac variables and gestational age observed in the NICOM‐specific reference ranges are consistent with previous findings, with increasing cardiac output values until around 35 weeks and a decrease thereafter until term, and decreasing SVR until around 36 weeks, followed by an increase towards 40 weeks. Stroke volume showed a small linear increase across gestation with lower variability in observations close to term. Maternal weight, height and age were associated with cardiac output (all P < 0.05) and SVR (all P < 0.01), whilst maternal weight and height were associated with stroke volume (both P < 0.001). Ethnicity was significantly associated with stroke volume ( P = 0.001) but not with cardiac output or SVR. Conclusions: This study presents device‐specific reference ranges for stroke volume, cardiac output and SVR for the NICOM device in healthy pregnancy and describes the maternal characteristics that are associated with the values of these hemodynamic measurements. Studies using NICOM in pregnancy can use these ranges in order to evaluate observations relative to those expected in uncomplicated pregnancy conditional on maternal characteristics. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.